Preparation method of CuCrZr alloy for fusion containing nano Y2O3 dispersion strengthening phase

CN122879542APending Publication Date: 2026-10-09SIRUI ADVANCED COPPER ALLOY TECH (FUFENG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611132092.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但现有制备技术存在直接混合熔炼时Y2O3纳米颗粒和Cu存在较大的密度差异导致Y2O3漂浮团聚,颗粒尺寸不均匀,强化效果不明显等问题

Benefits of technology

(1)本发明工艺显著提高铬锆铜材料高温力学性能及热导率:铬锆铜合金中添加纳米Y2O3弥散强化相后,合金400℃时的强度和抗热疲劳性能、热导率均得到明显提升,开发出一种兼顾高温强度、抗辐照性能、高导电导热性能以及低活化的适配可控核聚变服役工况的铬锆铜合金。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879542A_ABST
    Figure CN122879542A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a CuCrZr alloy for fusion containing a nano Y2O3 dispersion strengthening phase, and comprises the following steps: ingredient preparation according to mass percentage, respectively obtaining electrolytic copper plates, chromium blocks, copper-zirconium alloys, Y2O3 and Cu powder; then mixing Y2O3 and Cu powder according to a mass ratio of 1:4-6 to perform ball milling, forming Y2O3-Cu pre-composite powder with a Y2O3-Cu core-shell structure; selecting a vacuum furnace to perform smelting, adding the electrolytic copper plates in batches until the electrolytic copper plates are completely melted; then adding the chromium blocks until the chromium blocks are completely melted; reducing power and filling in argon, then increasing power to start refining, reducing power after completing the refining, and adding the copper-zirconium alloy and the Y2O3-Cu pre-composite powder, and starting casting within 3 min, taking out the furnace after the ingot is cooled, demolding after air cooling, and obtaining the CuCrZr alloy. The process can significantly improve the high-temperature mechanical properties and thermal conductivity of the chromium-zirconium-copper material, the prepared chromium-zirconium-copper alloy has strong organizational stability, and the strengthening phase is dispersedly distributed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of copper alloy preparation technology, specifically to a method for preparing CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase. Background Technology

[0002] In nuclear fusion reactors (such as ITER, CFETR in China, and EAST), key components such as the first wall, divertor, superconducting magnet armor, and heat sink assembly inside the vacuum chamber are installed inside the plasma vacuum chamber for extended periods, directly exposed to high-temperature plasma, and must withstand steady-state pressures of 10–20 MW / m³. 2 Extreme working conditions such as high heat load, 14 MeV high-energy neutron irradiation, strong magnetic field, and repeated thermal cycling (200–600℃) place extremely high demands on the thermal conductivity, high-temperature strength, structural stability, radiation resistance, and thermal fatigue resistance of materials.

[0003] Currently, fusion reactors such as EAST, ITER, and CFETR both domestically and internationally use traditional CuCrZr chromium-zirconium-copper alloys as the dedicated base material for the aforementioned high-heat-load components. This material possesses excellent room-temperature mechanical properties and thermal conductivity, meeting the basic requirements for conventional operation. However, as fusion reactors iterate towards long-pulse, steady-state, high-parameter operation, the high-temperature microstructure stability of traditional CuCrZr alloys is poor. In particular, when operating at 400℃, coarse Cr and Zr phases precipitate internally, causing high-temperature softening of the material. During thermal cycling, microcracks and fatigue damage are easily generated, leading to a significant reduction in component lifespan.

[0004] To address these shortcomings, the industry often employs Y2O3 nanoparticle dispersion strengthening to modify copper alloys. Utilizing Y2O3's grain boundary pinning and grain refinement properties, it can significantly improve the material's high-temperature strength and radiation resistance. However, existing preparation techniques suffer from problems such as the significant density difference between Y2O3 nanoparticles and Cu during direct mixing and melting, leading to Y2O3 floating and agglomeration, uneven particle size, and insignificant strengthening effect. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase.

[0006] The technical solution of this invention is: a method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase, comprising the following steps: S1. Ingredients: By mass percentage, the chromium content is 0.6%~0.9%, the zirconium content is 0.07%~0.15%, the yttrium content is 0.15%~0.4%, the impurities are ≤0.12%, and the balance is copper. Weigh each raw material to obtain electrolytic copper plate, chromium block, copper-zirconium alloy, Y2O3, and Cu powder, respectively, for later use; wherein, the mass ratio of Y2O3 to Cu powder is 1:4-6. S2, Y2O3-Cu pre-composite powder preparation (in-situ coating to prevent agglomeration): Y2O3 and Cu powder are mixed and ball-milled to form Y2O3-Cu pre-composite powder with a Y2O3-Cu core-shell structure; Y2O3 nanoparticles are used to disperse and strengthen the modified copper alloy. By utilizing their grain boundary pinning and grain refinement effects, the high-temperature strength and radiation resistance of the material can be significantly improved. S3. Semi-continuous casting: A vacuum furnace is used for melting. The vacuum level is evacuated to <10Pa. Electrolytic copper plates are added in batches and heated in a stepped manner until the electrolytic copper plates are completely melted. Then, chromium blocks are added and the temperature is raised to 1250-1300℃ until the chromium blocks are completely melted. The power is reduced to 100±10 kW, and argon gas is introduced and charged to -0.08MPa. The power is then increased to 600±10KW to start refining. The refining time is 30-35min. After refining, the power is reduced to 300±10KW, copper-zirconium alloy and Y2O3-Cu pre-composite powder are added, and casting begins within 3min to obtain CuCrZr alloy.

[0007] Furthermore, the purity of the electrolytic copper plate is ≥99.99%, the purity of the chromium block is ≥99.9%, the copper-zirconium alloy is CuZr40, and the Y2O3 is Y2O3 nanopowder (30-70 nm) or Y(OH)3 nanopowder (particle size 20-50 nm) with a purity ≥99.99%.

[0008] Furthermore, the Y2O3 is Y2O3 nanoparticles, and the ball milling method is as follows: Zirconia balls were used as the milling media, with a ball-to-material ratio of 8:1, and anhydrous ethanol was used as the dispersant. The ball mill speed was set to 300-400 r / min, and the milling time was 4-6 h, so that Y2O3 particles were uniformly coated on the surface of copper powder. Then, the powder was dried in a vacuum drying oven at 80℃ for 3 h. After removing the ethanol, the powder was passed through a 200-mesh sieve to obtain Y2O3-Cu pre-composite powder for later use.

[0009] Furthermore, the Y2O3 is Y(OH)3 nanoparticles, and the ball milling method is as follows: Zirconia balls were used as the milling media, with a ball-to-material ratio of 8:1. The ionic liquid [EMIM][Tf2N] (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt) was used as the dispersant. The ball mill speed was set to 350-450 r / min, and the milling time was 3-4 h. During the milling, low-temperature plasma (Ar / H2) coupled milling was used, with a power of 50-100 W and a pressure of 50 Pa. Subsequently, the mixture was pyrolyzed at 180-220℃ for 1-2 h under an inert atmosphere (Ar) to obtain Y2O3-Cu pre-composite powder for later use.

[0010] Explanation: During ball milling, Y(OH)3 is subjected to the synergistic effect of mechanical force and plasma, preferentially nucleating and dehydrating on the surface of Cu powder. The generated Y2O3 is directly anchored at the Cu lattice defects, which increases the interfacial bonding strength by more than 40%. By using 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt as a dispersant, which has the characteristics of high thermal stability (>300℃), low vapor pressure and strong polarity, it forms a monomolecular protective film through N+-Cu coordination adsorption, preventing Cu oxidation and reducing the surface energy of Y(OH)3, making it easier to spread evenly in ball milling. In addition, its high ionic conductivity can also couple with the plasma electric field to induce local electrochemical deposition effect and improve the coating kinetics of Y(OH)3. By using low-temperature plasma to excite active H· free radicals in the ball mill jar, the dehydration of Y(OH)3 is promoted, while the Cu surface is activated and the interfacial bonding is enhanced.

[0011] Meanwhile, H· can be an oxide on the Cu surface, exposing fresh active sites and promoting Y2O3 nucleation.

[0012] Furthermore, a static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.1-0.3 T; and Cu2S quantum dots (particle size 5-10 nm) are introduced into the ball mill jar, with the amount of Cu2S quantum dots introduced being 0.5-2.0 wt% of the Cu powder mass.

[0013] Explanation: A static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar. The Lorentz force is used to change the helical trajectory of electrons in the Ar / H2 plasma, causing H· radicals to be transported radially in a directional manner, forming a toroidal highly active region, as shown below:

[0014] This leads to the preferential adsorption and dehydration of the Y(OH)3 precursor on the {111} crystal plane of Cu powder, thereby achieving selective crystal plane strengthening.

[0015] Simultaneously, Cu2S quantum dots are introduced into the ball mill jar. Due to the copper vacancy defects, they possess a near-infrared LSPR response. Under high-energy electron excitation by plasma, a local electromagnetic field enhancement is generated on the surface of the quantum dots, inducing non-radiative decay and converting photon energy into transient nano-hot spots, which are achieved in the ball mill collision gap.

[0016] Meanwhile, Cu2S, as a p-type semiconductor, forms a Schottky junction with the Cu matrix, promoting electron transfer and stabilizing Y2O3 nucleation sites. Under the influence of a static magnetic field and the introduction of Cu2S quantum dots, the coating kinetics of Y(OH)3 are further enhanced, improving the effectiveness of Y2O3-Cu pre-composite powder in the preparation process of CuCrZr alloy.

[0017] Furthermore, the vacuum furnace adopts a stepped heating method, starting from 100KW and reaching a maximum of 500KW.

[0018] Note: Although electrolytic copper has high purity (≥99.9%), it still contains trace amounts of low-boiling-point impurities (such as Zn, Cd, Pb, and residual organic matter). A gradual temperature gradient is achieved through a stepped power increase (100 kW → 500 kW). 1) Low temperature section (100-200 kW): Maintain a vacuum of about 10 Pa to allow impurities with boiling points below 800℃ (such as Zn and Cd) to be preferentially vaporized and removed by the vacuum system; 2) Medium temperature range (300 kW): The temperature is raised to near the melting point of copper to promote the precipitation of gases such as hydrogen and oxygen from the melt; 3) High-temperature section (500 kW): Maintain high vacuum (<0.1 Pa) and hold for 20-30 minutes to allow residual gas and oxides to float to the surface and form slag, achieving deep degassing and deoxidation; This allows the copper plate to melt gradually from the surface inwards, avoiding localized overheating and violent churning of the molten pool, and ensuring a uniform temperature field in the melt.

[0019] Furthermore, before adding the copper-zirconium alloy and Y2O3-Cu pre-composite powder, a sample was taken from the furnace front. Based on the test results, the composition of the CuCrZr alloy was adjusted. Specifically, the Cr content in the CuCrZr alloy was adjusted. If the Cr content was too low, chromium blocks were added; if the Cr content was too high, electrolytic copper plates were added. The copper-zirconium alloy and Y2O3-Cu pre-composite powder were added only after the composition and temperature reached the appropriate range.

[0020] Explanation: By precisely controlling the atomic ratio of Cr to Zr in the CuCrZr matrix through pre-furnace sampling and analysis (e.g., Cr≈0.6–1.0 wt%, Zr≈0.08–0.15 wt%), in-situ nucleation of the Cu4Zr phase can be promoted, forming a coherent transition interface with Y2O3 (e.g., Y4Zr3O). 12 This significantly improves the dispersibility of Y2O3 in the copper matrix; through the synergistic regulation of composition and temperature, Y2O3 and the Cu matrix form a semi-coherent interface, reducing the interface energy and enhancing the interface bonding strength.

[0021] Furthermore, the casting process requirements are as follows: the casting power is 200 kW ± 10 kW, the ingot is cooled for 60 minutes before being taken out of the furnace, and it is air-cooled for ≥ 60 minutes before demolding; the casting should be slow at first, then fast, and then slow again, maintaining a uniform melt flow rate, with continuous flow throughout the process. When the casting is almost finished, the flow rate should be slowed down to reduce the depth of shrinkage cavities, and top-fill risers should be used to compensate for shrinkage.

[0022] Explanation: Slow initial pouring reduces the impact force of molten metal, avoids air entrapment and turbulence, and allows the temperature field inside the mold cavity to be established stably, laying the foundation for subsequent sequential solidification. As the casting is about to solidify, the flow rate is slowed down, allowing the molten metal in the riser to continuously feed the casting, prolonging the open time of the feeding channel, and causing shrinkage cavities to concentrate in the riser. This changes the shrinkage cavity shape from "V-shaped" to "U-shaped," significantly reducing the shrinkage cavity depth in the casting body and increasing density. The top-pour riser uses gravity to achieve solidification from top to bottom. Combined with slow final pouring, the feeding efficiency can be increased to 28-35%, and the yield can be increased by more than 15%.

[0023] The beneficial effects of this invention are: (1) The process of this invention significantly improves the high-temperature mechanical properties and thermal conductivity of chromium-zirconium-copper materials: After adding nano-Y2O3 dispersed strengthening phase to the chromium-zirconium-copper alloy, the strength, thermal fatigue resistance and thermal conductivity of the alloy at 400℃ are significantly improved. A chromium-zirconium-copper alloy that takes into account high-temperature strength, radiation resistance, high electrical and thermal conductivity and low activation is developed to be suitable for controlled nuclear fusion service conditions.

[0024] (2) The CuCrZr alloy prepared by the process of the present invention has strong structural stability: Y2O3 nanoparticles pin the grain boundaries, and the grains do not coarsen significantly under long-term high temperature and irradiation, with a service life of ≥5 years, reducing the replacement cost and downtime of fusion reactor components.

[0025] (3) The CuCrZr alloy prepared by the process of the present invention has a dispersed distribution of internal strengthening phase: Through the preparation method of in-situ reaction + vacuum induction melting, Y2O3 nanoparticles are uniformly dispersed in the CuCrZr matrix, which solves the technical bottlenecks of traditional materials such as low high-temperature strength, poor radiation resistance and unstable structure, and meets the service requirements of core components such as divertor, first wall and superconducting magnet armor in fusion reactor, further improving the alloy's high-temperature strength, thermal fatigue resistance and thermal conductivity. Attached Figure Description

[0026] Figure 1 This is a casting diagram of the CuCrZr alloy ingot containing the nano-Y2O3 dispersed strengthening phase of the present invention. Detailed Implementation

[0027] The present invention will now be described in more detail with reference to specific embodiments, so as to better demonstrate the advantages of the present invention.

[0028] Example 1: A method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase, comprising the following steps: S1. Ingredients: By mass percentage, the chromium content is 0.857%, the zirconium content is 0.011%, the yttrium content is 0.225%, the impurities are <0.05%, and the balance is copper. Weigh each raw material to obtain electrolytic copper plate, chromium block, copper-zirconium alloy, Y2O3, and Cu powder, respectively, for later use; wherein, the mass ratio of Y2O3 to Cu powder is 1:5. Wherein, the purity of the electrolytic copper plate is ≥99.99%, the purity of the chromium block is ≥99.9%, the copper-zirconium alloy is CuZr40, and the Y2O3 is Y2O3 nanopowder (30-70 nm) with a purity of ≥99.99%; S2, Y2O3-Cu pre-composite powder preparation (in-situ coating to prevent agglomeration): Y2O3 and Cu powder are mixed according to the mass ratio of Y2O3 to Cu powder in the above-mentioned ingredients and ball-milled to form Y2O3-Cu core-shell structure Y2O3-Cu pre-composite powder; using Y2O3 nanoparticles to disperse and strengthen the modified copper alloy, by utilizing its grain boundary pinning and grain refinement effect, the high temperature strength and radiation resistance of the material can be significantly improved; The ball milling method is as follows: Y2O3 and Cu powder are mixed and added to a planetary ball mill. Zirconia balls are used as the milling media, the ball-to-material ratio is 8:1, and anhydrous ethanol is used as the dispersant. The ball mill speed is set to 400 r / min, and the milling time is 4 h, so that the Y2O3 particles are uniformly coated on the surface of the copper powder. Then, the powder is dried in a vacuum drying oven at 80℃ for 3 h. After removing the ethanol, the powder is passed through a 200-mesh sieve to obtain Y2O3-Cu pre-composite powder for later use. S3. Semi-continuous casting: A vacuum furnace is used for melting. Electrolytic copper plates are added in stages, and a vacuum is drawn to <10Pa. Step heating begins, starting from 100KW and increasing to a maximum of 500KW until the electrolytic copper plates are completely melted. Then, chromium blocks are added, and the temperature is raised to 1280℃ until the chromium blocks are completely melted. The power is reduced to 100 kW, and argon gas is introduced to -0.08MPa. The power is then increased to 600 KW for refining, which takes 35 minutes. After refining, the power is reduced to 300 KW for temperature measurement and sampling. Samples are taken from the furnace and tested. Based on the test results, the composition of the CuCrZr alloy is adjusted. Specifically, the Cr content in the CuCrZr alloy is adjusted. If the Cr content is too low, chromium blocks are added; if the Cr content is too high, electrolytic copper plates are added. After the composition and temperature reach the appropriate range, copper-zirconium alloy and Y2O3-Cu pre-composite powder are added, and then... Casting begins within 1 minute with a casting power of 200 KW. The casting principle follows the principle of "slow first, then fast, then slow again". The flow rate is kept uniform and the process is continuous. When the casting is almost finished, the flow rate is slowed down to reduce the depth of shrinkage cavities. The top-fill riser is used to compensate for shrinkage. The ingot is removed from the furnace after cooling for 60 minutes and then demolded after air cooling for ≥60 minutes to obtain CuCrZr alloy.

[0029] Example 2: This example differs from Example 1 in that, by mass percentage, the chromium content is 0.85%, the zirconium content is 0.109%, the yttrium content is 0.236%, the impurities are <0.05%, and the balance is copper.

[0030] Example 3: This example differs from Example 1 in that, by mass percentage, the chromium content is 0.9%, the zirconium content is 0.098%, the yttrium content is 0.221%, the impurities are <0.05%, and the balance is copper.

[0031] Example 4: The difference between this example and Example 1 is that Y2O3 and Cu powder are mixed at a mass ratio of 1:4 and ball-milled to form Y2O3-Cu precomposite powder with a Y2O3-Cu core-shell structure.

[0032] Example 5: The difference between this example and Example 1 is that Y2O3 and Cu powder are mixed at a mass ratio of 1:6 and ball-milled to form Y2O3-Cu precomposite powder with a Y2O3-Cu core-shell structure.

[0033] Example 6: The difference between this example and Example 1 is that the ball mill speed is set to 300 r / min and the ball milling time is 5 h, so that Y2O3 particles are uniformly coated on the surface of copper powder to form Y2O3-Cu precomposite powder with Y2O3-Cu core-shell structure.

[0034] Example 7: The difference between this example and Example 1 is that the ball mill speed is set to 400 r / min and the ball milling time is 6 h, so that Y2O3 particles are uniformly coated on the surface of copper powder to form Y2O3-Cu precomposite powder with Y2O3-Cu core-shell structure.

[0035] Example 8: This example differs from Example 1 in that a vacuum furnace is used for melting. Electrolytic copper plates are added in stages, and a vacuum is drawn to a degree of <10 Pa. Step heating begins, starting from 100 KW and increasing to a maximum of 500 KW until the electrolytic copper plates are completely melted. Then, chromium blocks are added, and the temperature is raised to 1250℃ until the chromium blocks are completely melted. The power is reduced to 90 kW, and argon gas is introduced and charged to -0.08 MPa. The power is then increased to 590 KW to begin refining, which takes 30 minutes. After refining, the power is reduced to 290 KW for temperature measurement and sampling. The sample taken from the furnace is tested, and the composition of the CuCrZr alloy is adjusted according to the test results. Once the composition and temperature reach the appropriate range, copper-zirconium alloy and Y2O3-Cu pre-composite powder are added, and casting begins within 3 minutes at a casting power of 190 KW.

[0036] Example 9: This example differs from Example 1 in that a vacuum furnace is used for melting. Electrolytic copper plates are added in stages, and a vacuum is drawn to a degree of <10 Pa. Step heating begins, starting from 100 KW and increasing to a maximum of 500 KW until the electrolytic copper plates are completely melted. Chromium blocks are then added, and the temperature is raised to 1300℃ until the chromium blocks are completely melted. The power is reduced to 110 kW, and argon gas is introduced until it reaches -0.08 MPa. The power is then increased to 610 KW to begin refining, which takes 35 minutes. After refining, the power is reduced to 310 KW for temperature measurement and sampling. Samples are taken from the furnace and tested. The composition of the CuCrZr alloy is adjusted based on the test results. Once the composition and temperature reach the appropriate range, copper-zirconium alloy and Y2O3-Cu pre-composite powder are added, and casting begins within 3 minutes at a casting power of 210 KW.

[0037] Example 10: This example differs from Example 1 in that the Y2O3 is Y(OH)3 nanoparticles (particle size 20-50 nm) with a purity ≥99.99%. The ball milling method is as follows: Y2O3 and Cu powder are mixed and added to a planetary ball mill (an existing planetary ball mill, such as the Adecco Instruments 430 r / min model, can be equipped with a closed plasma generation module and an ionic liquid circulating cooling system without replacing the main unit, resulting in low modification costs). Zirconia balls are used as the milling medium, with a ball-to-material ratio of 8:1. The ionic liquid [EMIM][Tf2N] (1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt) is used as the dispersant. The ball mill speed is set to 400 r / min, and the milling time is 3 h. During this period, low-temperature plasma (Ar / H2, 10:1) is used to couple the ball milling. The power of the low-temperature plasma is 75 W, and the pressure is 50 Pa. Subsequently, the powder is pyrolyzed at 200℃ for 1 h under an inert atmosphere (Ar) to obtain Y2O3-Cu pre-composite powder for later use.

[0038] Example 11: The difference between this example and Example 10 is that the ball mill speed is set to 350 r / min and the ball milling time is 4 h.

[0039] Example 12: The difference between this example and Example 10 is that the ball mill speed is set to 450 r / min and the ball milling time is 3 h.

[0040] Example 13: This example differs from Example 10 in that it uses low-temperature plasma (Ar / H2) coupled ball milling, with a low-temperature plasma power of 50 W and a gas pressure of 50 Pa.

[0041] Example 14: This example differs from Example 10 in that it uses low-temperature plasma (Ar / H2) coupled ball milling, with a low-temperature plasma power of 100 W and a gas pressure of 50 Pa.

[0042] Example 15: This example differs from Example 10 in that it is subsequently pyrolyzed at 180°C for 1.5 h under an inert atmosphere (Ar) to obtain Y2O3-Cu precomposite powder.

[0043] Example 16: The difference between this example and Example 10 is that the Y2O3-Cu precomposite powder was subsequently obtained by low-temperature pyrolysis at 220°C for 2 h under an inert atmosphere (Ar).

[0044] Example 17: This example differs from Example 10 in that a static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.2 T; and Cu2S quantum dots (particle size 5-10 nm) are introduced into the ball mill jar. Specifically, in the initial feeding stage, they are added to the ball mill jar simultaneously with Y(OH)3 and Cu powder, and the amount of Cu2S quantum dots introduced is 1.8 wt% of the mass of Cu powder.

[0045] Example 18: The difference between this example and Example 17 is that a static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.1 T.

[0046] Example 19: This example differs from Example 17 in that a static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.3 T.

[0047] Example 20: This example differs from Example 17 in that the amount of Cu2S quantum dots introduced is 0.5 wt% of the mass of Cu powder.

[0048] Example 21: This example differs from Example 17 in that the amount of Cu2S quantum dots introduced is 2.0 wt% of the mass of Cu powder.

[0049] Experimental Example: The properties of chromium-zirconium-copper alloy materials were investigated. The following are the ingot compositions with different contents of chromium, zirconium, and yttrium, as shown in Table 1: Table 1. Composition of Chromium-Zirconium-Copper Alloy Ingots

[0050] The chromium-zirconium-copper alloys obtained in Experimental Examples 1-3 (prepared using the process of Example 1) and Comparative Examples 1-2 (both prepared using the same process as Example 1, except that no S2 was introduced (Y2O3 was not introduced)) were subjected to high-temperature (400℃) tensile strength, yield strength, and elongation tests. The results are shown in Table 2 below: Table 2. Experimental results of various chromium-zirconium-copper alloy ingots

[0051] As can be seen from the results in Table 2 above, the tensile strength, yield strength, elongation and thermal conductivity of the chromium-zirconium copper alloy ingot prepared by the process of the present invention are significantly improved compared with comparative examples 1-2. It can be seen that the introduction of an appropriate amount of yttrium into the chromium-zirconium copper alloy can significantly enhance the performance of the chromium-zirconium copper alloy ingot.

[0052] Meanwhile, to investigate the impact of yttrium introduction methods on the performance of zirconium-copper alloy ingots, the following comparison is presented in Table 3: Table 3. Effects of different yttrium introduction methods on the performance indicators of Y2O3-Cu precomposite powder

[0053] It should be noted that Scheme I is as follows: "Zirconium oxide balls are used as the ball milling media, with a ball-to-material ratio of 8:1, and anhydrous ethanol is used as the dispersant; the ball mill speed is set to 300-400 r / min, and the ball milling time is 4-6 h, so that Y2O3 particles are uniformly coated on the surface of copper powder; then, the powder is dried in a vacuum drying oven at 80℃ for 3 h, and after removing the ethanol, it is passed through a 200-mesh sieve to obtain Y2O3-Cu pre-composite powder."

[0054] Scheme II is as follows: "Zirconium oxide balls are used as the ball milling media, with a ball-to-material ratio of 8:1. Ionic liquid [EMIM][Tf2N] is used as the dispersant. The ball mill speed is set to 350-450 r / min, and the ball milling time is 3-4 h. During this period, low-temperature plasma coupling ball milling is used, with a low-temperature plasma power of 50-100 W and a gas pressure of 50 Pa. Subsequently, low-temperature pyrolysis is carried out at 180-220℃ for 1-2 h under an inert atmosphere to obtain Y2O3-Cu precomposite powder."

[0055] Scheme III is as follows: "Zirconium oxide balls are used as the milling media, with a ball-to-material ratio of 8:1. Ionic liquid [EMIM][Tf2N] is used as the dispersant, and Cu2S quantum dots are introduced. The amount of Cu2S quantum dots introduced is 0.5-2.0 wt% of the Cu powder mass. A static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.1-0.3 T. The ball mill speed is set to 350-450 r / min, and the ball milling time is 3-4 h. During this period, low-temperature plasma coupling ball milling is used, with a low-temperature plasma power of 50-100 W and a gas pressure of 50 Pa. Subsequently, low-temperature pyrolysis is carried out at 180-220℃ for 1-2 h under an inert atmosphere to obtain Y2O3-Cu pre-composite powder."

[0056] Taking the composition of the chromium-zirconium-copper alloy ingot in Experiment Example 1 as an example, the chromium-zirconium-copper alloys prepared by Scheme I, Scheme II, and Scheme III were tested for high-temperature (400℃) tensile strength, yield strength, and elongation. The results are shown in Table 4 below: Table 4. Experimental results of various chromium-zirconium-copper alloy ingots

[0057] As can be seen from the results in Table 4 above: 1) By comparing Scheme II with Scheme I, it can be seen that after replacing the original Y2O3 nanopowder with Y(OH)3 nanopowder, the interfacial bonding strength can be significantly improved, thereby making the Y element uniformly dispersed in the CuCrZr matrix, improving the effect of introducing the Y element into the chromium zirconium copper alloy ingot, and significantly enhancing the performance of the chromium zirconium copper alloy ingot.

[0058] 2) A comparison between Scheme III and Scheme II shows that, based on Scheme II, applying a static magnetic field perpendicular to the rotation axis outside the ball mill jar and introducing Cu2S quantum dots can further improve the effect of introducing Y element into the chromium-zirconium-copper alloy ingot. It can be seen that by utilizing the Lorentz force to change the helical motion trajectory of electrons in the Ar / H2 plasma, H· radicals can be transported radially in a directional manner to form a ring-shaped high-activity region, achieving selective strengthening of crystal planes. Furthermore, Cu2S, as a p-type semiconductor, can form a Schottky junction with the Cu matrix, promoting electron transfer and stabilizing Y2O3 nucleation sites. Under the influence of the static magnetic field and the introduction of Cu2S quantum dots, the coating kinetics of Y(OH)3 are further enhanced, improving the effectiveness of Y2O3-Cu pre-composite powder in the CuCrZr alloy preparation process.

Claims

1. A method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed reinforcing phase, characterized in that, Includes the following steps: S1. Ingredients: By mass percentage, the chromium content is 0.6%~0.9%, the zirconium content is 0.07%~0.15%, the yttrium content is 0.15%~0.4%, and the balance is copper. Weigh each raw material to obtain electrolytic copper plate, chromium block, copper-zirconium alloy, Y2O3, and Cu powder, respectively, for later use; wherein, the mass ratio of Y2O3 to Cu powder is 1:4-6. Preparation of S2 and Y2O3-Cu precomposite powder: Y2O3 and Cu powder are mixed and ball-milled to form Y2O3-Cu precomposite powder with Y2O3-Cu core-shell structure; S3. Semi-continuous casting: A vacuum furnace is used for melting. The vacuum is evacuated to <10Pa. Electrolytic copper plates are added in batches and heated in a stepped manner until the electrolytic copper plates are completely melted. Then, chromium blocks are added and the temperature is raised to 1250-1300℃ until the chromium blocks are completely melted. Then, the power is reduced to 100±10 kW and argon gas is introduced. The pressure is raised to -0.08 MPa and then the power is increased to 600±10 kW to start refining for 30-35 minutes. After refining, the power is reduced to 300±10 kW, copper-zirconium alloy and Y2O3-Cu pre-composite powder are added, and casting begins within 3 minutes to obtain CuCrZr alloy.

2. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, The electrolytic copper plate has a purity of ≥99.99%, the chromium block has a purity of ≥99.9%, the copper-zirconium alloy is CuZr40, and the Y2O3 is Y2O3 nanopowder or Y(OH)3 nanopowder with a purity of ≥99.99%.

3. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, The Y2O3 is Y2O3 nanoparticles, and the ball milling method is as follows: Zirconia balls were used as the milling media, with a ball-to-material ratio of 8:1, and anhydrous ethanol was used as the dispersant. The ball mill speed was set to 300-400 r / min, and the milling time was 4-6 h, so that Y2O3 particles were uniformly coated on the surface of copper powder. Then, the powder was dried in a vacuum drying oven at 80℃ for 3 h. After removing the ethanol, the powder was passed through a 200-mesh sieve to obtain Y2O3-Cu pre-composite powder for later use.

4. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, The Y2O3 is Y(OH)3 nanoparticles, and the ball milling method is as follows: Zirconia balls were used as the milling media, with a ball-to-material ratio of 8:

1. The ionic liquid [EMIM][Tf2N] was used as the dispersant. The ball mill speed was set to 350-450 r / min, and the milling time was 3-4 h. During the milling process, low-temperature plasma-coupled milling was used, with a plasma power of 50-100 W and a pressure of 50 Pa. Subsequently, the mixture was pyrolyzed at 180-220℃ for 1-2 h under an inert atmosphere to obtain Y2O3-Cu pre-composite powder for later use.

5. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 4, characterized in that, A static magnetic field perpendicular to the rotation axis is applied outside the ball mill jar, with a magnetic field strength of 0.1-0.3 T; and Cu2S quantum dots are introduced into the ball mill jar, with the amount of Cu2S quantum dots introduced being 0.5-2.0 wt% of the Cu powder mass.

6. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, The electrolytic copper plate is added in stages and heated in a stepped manner until the electrolytic copper plate is completely melted. The stepped heating method is as follows: start heating from 100KW and go up to 500KW.

7. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, Before adding copper-zirconium alloy and Y2O3-Cu pre-composite powder, samples were taken from the furnace front. Based on the test results, the Cr content in the CuCrZr alloy was adjusted. If the Cr content was too low, chromium blocks were added; if the Cr content was too high, electrolytic copper plates were added.

8. The method for preparing a CuCrZr alloy for fusion containing a nano-Y2O3 dispersed strengthening phase according to claim 1, characterized in that, The casting process requirements are as follows: the casting power is 200 kW ± 10 kW, the ingot is removed from the furnace after cooling for 60 minutes, and it is demolded after air cooling for ≥ 60 minutes.